Serum levels of IL-6 are associated with cognitive impairment in the salus in apulia population-based study. Issue 3 (March 2023) - Griseta, Chiara; Battista, Petronilla; Castellana, Fabio; Colonna, Isabella; Sciarra, Sabrina; Zupo, Roberta; Bortone, Ilaria; Lampignano, Luisa; Tirelli, Sarah; Berardino, Giuseppe; Mollica, Anita; Lozupone, Madia; et al.
Abstract: Growing evidence suggests that inflammation contributes to brain aging and neurodegeneration. This study investigates the relationship between global cognitive as well executive function and the inflammatory markers IL-6, CRP, and TNF-α in a population-based study of older adults. A population-based sample, of older people in Southern Italy, was enrolled. We measured serum levels of IL-6, CRP, and TNF-α. We also administered two neuropsychological tests: Mini-Mental State Examination and Frontal Assessment Battery. Rank-based regression models were performed to investigate the relationship between inflammatory markers and cognitive functions, including major demographic and clinical confounders for adjustment. The sample consisted of 1929 subjects aged between 65 and 95 years. Multivariate linear regression analysis revealed that higher serum levels of IL-6 were associated with lower MMSE and FAB scores even after adjustment for demographic data and cardiovascular risk factors. No significant associations were found between cognitive functioning and serum levels of CRP and TNF-α. Our results suggest that higher levels of IL-6 were associated with cognitive impairment in an older adult population of Southern Italy.